Cooperation between the United Nations High Commissioner for Refugees and international and non-governmental organisations to address the issue of forced migration in Africa in the 1990s - Selivanov, Andrey V. (Journal of the Belarusian State University. History, 2025)
This article analyses the reports of the UN High Commissioner for Refugees presented to the 46–66th UN General Assembly sessions. Particular attention is given to the cooperation between the Office of the UN High Commissioner for Refugees and UN system agencies, as well as international, regional, and non-governmental organisations, aimed to address the challenges of forced migration in Africa during the 1990s. The research concludes that inter-agency cooperation of UN High Commissioner for Refugees evolved throughout the analysed period from the provision of emergency assistance to refugees to active involvement in repatriation and support for development both in areas of return and in the communities left behind. The international community demonstrated effective collaboration in tackling the issues of forced migration in Africa. It is argued that, given sufficient political will to resolve protracted conflicts and prevent new ones, current challenges related to forced migration can be addressed far more effectively.